Relationship of Smoking Risk Factors and Comorbids with Covid-19 Mortality: Systematic Review and Meta-Analysis - Dien Gusta Anggraini Nursal; Yessy Markolinda; Masrizal Masrizal; Yusmayanti Yusmayanti; Imraatul Hasni (Jurnal Kesehatan Masyarakat Andalas, 2022)
The COVID-19 outbreak that began in December 2019 in Wuhan, China has become a pandemic. The whole world is struggling to fight against COVID-19, every effort has been made. In addition, this disease also has various risk factors in the form of characteristics and comorbidities of the disease. The study aimed to examine the relationship between smoking and comorbidities with COVID-19 mortality using a systematic review and meta-analysis. ,13-1,22). Comorbid diabetes mellitus had a significant relationship with mortality with a p-value of 0.00001 (OR 2.45 95% CI 1.55-3.88). Hypertension has a significant relationship with mortality with a p-value of 0.0001 (OR 3.88 95% CI 0.92-16.44). Cardiovascular has a significant relationship with mortality with a p-value of 0.005 (OR 3.77 95% CI 1.51-9.43). COPD has a significant relationship with mortality with a p-value of 0.00001 (OR 4.68 95% CI 3.11-7.04). Factors for mortality risk factors for smoking, diabetes mellitus, hypertension, cardiovascular and COPD have a significant relationship and can increase the risk of death in patients with COVID-19